Good IPOs Draw in Bad: Inelastic Banking Capacity and Hot Markets - Khanna, Naveen; Noe, Thomas H.; Sonti, Ramana (Review of Financial Studies, 2008)
[We posit that screening IPOs requires specialized labor which is in fixed supply. A sudden increase in demand for IPO financing increases the compensation of IPO screening labor. This results in reduced screening, encouraging sub-marginal firms to enter the IPO market, further fueling the demand for screening labor. The model's conclusions are consistent with empirical findings of increased underpricing during hot markets, positive correlation between issue volume and underpricing, and with tipping points between hot and cold markets. Finally, the model makes sharp predictions relating the IPO market to fundamental values of firms and to investment banking returns.]